Environmental Factors and Survey Research in Developing Countries: Evidence from Nigeria - L, Raimi; M. A, Adebakin; W.O, Gabadeen (Asian Journal of Empirical Research, 2013)
Survey research is relevant and appropriate for problem identification and provision of objective explanations to hidden phenomena of interest to researchers. Despite the preference for surveys by researchers in the fields of social sciences, management and educational management, it is a research strategy that is confronted by a number of environmental factors. The present study examines the impact of these factors on surveys in Nigeria using a quantitative method. The required data were collected using a survey evaluation instrument (SEI) which contained 33 items. The sample size of 250 lecturers, researchers and students was selected from the target population using a purposive sampling technique. The generated data were analyzed using descriptive and inferential statistics on the basis of which informed conclusions were drawn. The findings indicate that surveys are hindered by low literacy level of respondents, multiplicity of ethnic groups/languages, respondents’ inability of respondents to answer survey questions appropriately, incidences of misleading responses and several other environmental factors. The paper concludes that if the observed environmental factors are substantially redressed, survey research in Nigeria would be greatly enriched and the research findings therefrom would be better fortified.